COMPARATIVE ANALYSIS OF HUMAN FEEDBACK AND AI FEEDBACK GRAMMATIC STRUCTURE - Normamatova Zakhro Dilshodovna (Modern American Journals, 2025)
This artucle explores the grammatical characteristics of feedback provided by human instructors versus artificial intelligence (AI) systems, with a particular focus on sentence structure, modality, tone, and complexity. Drawing from a corpus of real-world feedback samples from classrooms and language learning platforms (such as ChatGPT and Grammarly), the research analyzes structural tendencies, identifies syntactic patterns, and evaluates the communicative effectiveness of each source. While human feedback tends to favor elliptical, affective, and context-aware constructions, AI feedback is marked by consistency, completeness, and formal syntax. This contrast reflects not only grammatical structure but also deeper cognitive and pragmatic differences between human and machine-generated language. The study aims to contribute to the growing field of AI-mediated education by providing linguistic insights into the feedback dynamic.
Keywords: AI feedback, human feedback, grammar, sentence structure, modality, tone, syntax, educational technology, language learning, communication